The Impact of Training and Development Methods on Employee Productivity in the Insurance Industry - Sharmila, Ratnam (Universiti Malaysia Sarawak (UNIMAS), 2020)
The purpose of this study is to investigate the impact of training and development methods and employee’s productivity in the insurance industry, Negeri Sembilan, Malaysia. Data were gathered from 50 insurance agents from Zurich Insurance Company in Negeri Sembilan. The quantitative research methodology is used in this research and data were collected using a google form survey questionnaire as the instrument. The analysis of data and information was done using the Statistical Package for Social Science (SPSS). The data were analyzed using descriptive and inferential statistics. Descriptive statistics were reported, followed by hypothesis testing using Pearson correlation and Multiple regression. This data was collected by this research and was analyzed using the Statistical Package for Social Science (SPSS). The findings have shown that there is a very strong relationship between training and development methods and employee’s productivity in the insurance industry in Negeri Sembilan. Besides, findings from this study also indicated that job rotation is the most dominant method among independent variables. The study contributes to the existing pool of knowledge to the insurance agents in Malaysia. On the other hand, the result of this study could help the organization to improve the training and development methods to ensure the organizations can achieve employee’s productivity.